Indicators Related to The Words of Turkish Languages (Zien Journal of Social Sciences and Humanities, 2021)
To date, a number of scientific research on toponymy has been carried out in the country. They to some extent express their views on the geographical terms, including the active participation in their formation, as well as on the differences in the toponymic indicators that are part of such terms. However, the issue of toponymic indicators in Karakalpak linguistics is poorly studied. This is because the lexical units included in this group are of great importance in the study of geographical terms. Their scientific research provides a wealth of information about the evolution of different affixes in the modern Karakalpak language and the stages of development, the old methods of word formation, phonetic phenomena that are characteristic of a particular region. However, research in this area is not enough. It has many unresolved issues. This emphasizes the relevance of the topic of this master's dissertation.